KAJIAN TEKNOLOGI PEMBUATAN TEPUNG KACANG HIJAU INSTAN DAN SIFAT FISIK - Nurhidajah .; Waysima .; Nur Wulandari (Jurnal Pangan dan Gizi, 2010)
The purpose of this research was studied the effect of soaking solution and stripping the treatment of the physical characteristics of mung bean flour produced. The design of this study is purely experimental descriptive analytic method. Research done in 2 stages: a preliminary study and main study. Preliminary research to find the optimal soaking time, ie variation of immersion time. Primary research to find the characteristics of various soaking solutions (aquades, Na2HPO4, and mixtures of Na-citrate- Ca(H2PO4)2 and control). The variables measured were the development of the volume ratio, water absorption ratio, yield, density Kamba, when soluble, starch granules are microscopic, whiteness and water absorption index. The results showed that immersion using a mixture of of Na-citrate- Ca (H2PO4)2 ratio of 1:1 in 1% concentration and immersion time of 11 hours gives the results of the physical characteristics of the best instant mung bean flour. Key words: mung beans, flour, instant, cooking technology.